2009
DOI: 10.1007/s10531-009-9718-z
|View full text |Cite
|
Sign up to set email alerts
|

Birds nesting survival in disturbed and protected Neotropical savannas

Abstract: Fragmentation and other habitat disturbances are long known to negatively affect birds, in large part by decreasing nest success due to high nest predation rates. The factors, however, that cause this decrease in nest success are still poorly understood and may vary among regions or species. Here, we show that nest survival is also lower in a disturbed landscape versus a protected cerrado (savanna-like) Neotropical landscape. Also, we tested the importance of garbage in the nest, brood parasitism, microhabitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 63 publications
(61 reference statements)
2
32
2
2
Order By: Relevance
“…Our results are contrary to what has been found in other studies in the central cerrado region (Santos, 2008;Borges and Marini, 2010) and other seasonal environments in the temperate zone (e.g. Hochachka, 1990;Verhulst et al, 1995).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are contrary to what has been found in other studies in the central cerrado region (Santos, 2008;Borges and Marini, 2010) and other seasonal environments in the temperate zone (e.g. Hochachka, 1990;Verhulst et al, 1995).…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study showed similar tendency for large eggs (quail eggs; França & Marini 2009a). Surprisingly, studies of natural nests in the same region found declining nest survival rates as the breeding season progressed (Borges & Marini 2010, Santos 2008. Artificial nests may be inaccurate for providing absolute nest predation rates on real nests, but may be sufficient for relative comparisons (Major & Kendal 1996, Buler & Hamilton 2000, Dion et al 2000.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, in some areas in the Cerrado, birds were the main predators (França et al 2009). Overall, predation in the Cerrado habitats tended to increase throughout the reproductive period (Borges & Marini 2010), decrease during nest development (França & Marini 2009b), and differ between habitats and microhabitats (França & Marini 2009a, Borges & Marini 2010. These studies show the importance of predation for population dynamics of neotropical birds and so experiments with artificial nests may be important to understand spatial and temporal patterns of reproductive success.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations